Epidemiology and determinants of chronic migraine: A real-world cohort study, with nested case-control analysis, in primary care in Italy. (April 2020) - Marconi, Ettore; Pecchioli, Serena; Nica, Mihaela; Colombo, Delia; Mazzoleni, Francesco; De Cesaris, Francesco; Geppetti, Pierangelo; Cricelli, Claudio; Lapi, Francesco
Background: The proper identification of chronic migraine is one of the mainstays for general practitioners. This study therefore aims to assess the epidemiology and determinants of chronic migraine in primary care in Italy by testing five operational case definition algorithms. Methods: Five case definition algorithms defining chronic migraine were developed to estimate the prevalence and incidence rate of chronic migraine in the Health Search database. For each algorithm, we conducted a nested case-control analysis to quantify the level of association between certain determinants and incident cases of chronic migraine. Results: Considering a cohort of 1, 091, 032 patients (52% were females), the prevalence rate of chronic migraine increased from the first to the fifth case definition algorithm ranging from 0.03 to 0.28%. No 95% confidence interval overlapped the others, and every confidence interval reliably maintained 2% precision. Incidence rates showed a growing trend (0.008–0.056 per 100, 000 person-years) as well. All case definition algorithms were able to capture sex (i.e. female) and nonsteroidal anti-inflammatory drug (NSAID) overuse as statistically significant determinants of incident cases of chronic migraine. Depression was associated with a statistically significant increase of incidence rate of chronic migraine only for two case definition algorithms. Conclusion: Our findings show that prevalence and incidence rate of chronic migraine are underestimated when compared with current literature. On the other hand, we found acceptable correctness of chronic migraine definition in the light of the association with well-known determinants.